Mechanical properties of the FFF sandwich-structured parts made of PLA/TPU multi-material - Arifvianto, Budi; Satiti, Baikhati E.; Salim, Urip A.; Suyitno, Suyitno; Nuryanti, Archadian; Mahardika, Muslim (Springer Nature, 2022)
Currently, multi-material approach has become an interesting research subject in the field of materials engineering and additive manufacturing technology. With this technique, the properties of a 3D-printed material could be tailored by combining two or more dissimilar materials with certain configurations such as the sandwich structures. So far, the studies concerning such sandwich-structured FFF multi-material system is, however, still lacking. In this research, mechanical properties of the sandwich-structured FFF-processed multi-material parts composed of a rigid polylactic acid (PLA) and a flexible thermoplastic polyurethane (TPU) were determined. Three groups of specimens with various sandwich configurations were examined in terms of their maximum tensile strength, strain at break and elastic modulus. In addition, a Shore D hardness analysis was carried out to point out the benefits of having the multi-material structure in the FFF-processed polymeric material. The result of this study showed that the combination of PLA/TPU in a sandwich form could improve the low strength and elastic modulus of an FFF-processed monolithic TPU elastomer. In this case, the tensile strength and elastic modulus of the sandwich-structured PLA/TPU multi-material were higher than those of the printed monolithic TPU. However, this strategy was not successful for improving the low strain-at-break possessed by the FFF printed monolithic PLA material. On the basis of the analysis over the fractured surface of the specimen, the low affinity and low compatibility between the deposited PLA and TPU material obviously caused the failure of this sandwich-structured FFF-processed PLA/TPU multi-material. © 2022, The Author(s), under exclusive licence to Springer Nature Switzerland AG.